Benzophenone Suppression of Quercetin Antioxidant Activity towards Lipids under UV-B Irradiation Regime: Detection by HPLC Chromatography - Jelena S. Stanojević; Dejan Z. Marković; Jelena B. Zvezdanović (Journal of Chemistry)
Quercetin, a well-known flavonoid antioxidant, has been employed to control benzophenone-sensitized peroxidation of the lipid mixture in methanol solution, induced by continuous UV-B irradiation. Surprisingly, the detected quercetin antioxidant activity was almost negligible. The presented data suggests that the reason is not in its own UV-B-induced degradation but rather in its interrelationship with benzophenone during UV-B stress. On the other side of this relationship, benzophenone anticipated sensitizing role towards lipids; that is, the initiation of lipid peroxidation has been affected as well. These results, obtained by HPLC chromatography, partly confirm but partly relativize to some extent recent results obtained with the same system by spectrophotometric method.